Improving Safe Mobility: An Assessment of Vehicles and Technologies among a Large Cohort of Older Drivers. Issue 1 (2nd January 2019) - Zanier, Nicole; Molnar, Lisa J.; Eby, David W.; Kostyniuk, Lidia P.; Zakrajsek, Jennifer S.; Ryan, Lindsay H.; St. Louis, Renée M.; Stanciu, Sergiu C.; LeBlanc, David J.; Smith, Jacqui; Yung, Raymond; Nyquist, Linda V.; et al.
Abstract: Evidence suggests that older driver safety may be improved by good vehicle maintenance, in-vehicle advanced technologies, and proper vehicle adaptations. This study explored the prevalence of several measures of vehicle maintenance and damage among older drivers through inspection of their vehicles. We also investigated the prevalence of in-vehicle technologies and aftermarket adaptations. Vehicle inspections were conducted by trained research staff using an objective, standardized procedure. This procedure, developed by a multidisciplinary team of researchers, was based on a review of inspection checklists used by automobile dealerships and the project team's expertise. The study used baseline data from vehicles of 2988 participants in the multi-site Longitudinal Research on Aging Drivers (LongROAD) study. Among this cohort, vehicles were well maintained, had little damage, and contained a range of advanced technologies but few aftermarket adaptations. Implications of study findings for occupational therapy practice are discussed.